(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the types of xenobiotics that harm our health in our daily lives and the damage they cause and the body’s defense mechanisms against these toxins, methods of studying some xenobiotics and 2 types of protective barriers in the body.